PENGARUH LATIHAN VARIASI DRILL MENGGIRING BOLA TERHADAP KELINCAHAN MENGGIRING BOLA PEMAIN BAKTI RAYA FC PEKANBARU - Fernando, Taufik; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: From the results of the observetion in the field, the Bakti Raya FC Pekanbaru Football Team still lacks when ball dribbling is affected because of the frequent loss of the ball when dribbling the ball, and when dribbling the position of the foot and ball is too far away, and the player is less agile when dribbling the ball. One effort to improve the agility of dribbling correctly is an effective and efficient exercise. Therefore this researcher aims to measure the agility of dribbling on Bakti Raya players F.C because this football team must be emphasized on the basic techniques of dribbling. This research is an experimental research. This research was carried out by the Bakti Raya Football Team FC Pekanbaru. Data were obtained and collected through initial tests and final tests before and after conducting drill variation exercises. The data obtained were analyzed descriptively. From the results of data analysis shows that there is a significant influence between drill variation training methods on agility to dribble the players of the Bakti Raya FC Pekanbaru team. Based on the results of statistical analysis of the test t value of Tcount 11.2> T table 1.792. at a significant level of 0.05. Means Thitung> Ttabel so that it can be concluded that There is a Significant Effect of Drill Variation Exercises Herding the Ball (X) Against Agility (Y) Herding Bakti Raya Player Ball FC Pekanbaru.Keywords: Dribble, Agility, Drill Variation